Development of Spectral Delayed Luminescence System for Whole Saliva Analysis: A Prototype Study (Jurnal Teknologi (Sciences & Engineering), 2014)
This paperwork presents the development of spectral delayed luminescence system for the measurement of whole saliva. Despite various reports of delayed luminescence and its correlation to various diseases, it has fail to highlight the specific cause of the occurrence suggesting it being more suitable as a screening tool utilizing saliva as non-invasive sampling medium. Therefore it is the aim of this paper to have the system critical performance tested before putting it to use at the field. The system prototype is tested for its response during room temperature operation and during spot cooling of the photomultiplier tube module. Delayed luminescence of saliva is compared over distilled water as a control. The spectral delayed luminescence of saliva is compared to that of the dimmed white light for functional testing purposes. Through experiments, the best operation for the system is at constant room temperature with light stimulation time determined at 150 ms. Being 98% water, the delayed luminescence of saliva is slightly greater than that of distilled water. Given light stimulation of wide spectrum from white LED, the delayed luminescence of saliva is accumulated between 495 nm and 530 nm. Results demonstrated that the system for spectral delayed luminescence of saliva is viable and capable for acquiring data for further studies.Â